ANALISIS STRATEGI PENGEMBANGAN USAHA INDUSTRI KECIL SOUVENIR DI KELURAHAN PENGGILINGAN KECAMATAN CAKUNG KOTA ADMINISTRASI JAKARTA TIMUR TAHUN 2012 - Novia Maya Riyanzie (Economics Development Department, Universitas Negeri Semarang, Indonesia, 2013)
The purposes from this research are to know power, weakness, opportunity and threat by small souvenirs industry and to know the strategy development used. The method used in this research is descriptive method among 39 souvenirs entrepreneurs. The variables are finances, workers, technologies, and markets. There are two kinds analysis methods that used in this research, descriptive analysis and SWOT analysis. The results shows small souvenirs industry in Kelurahan Penggilingan Kecamatan Cakung Kota Administrasi Jakarta have powers, shows from the high quality value and high art value. Otherwise the weakness is the limit of managerial skill to handle this business. There are some opportunity from this kinds of industry such as good promotion and open market. There is a threat from this business unstable condition venture. Some kinds strategy could use in this field business is concentration strategy by horizontal strategy that mean a strategy used more defensive, mean avoid losing in selling and avoid losing profit.